Enhancement of wheat productivity through variation in sowing time and nutrient management with growth regulators - Dhiman Mukherjee (Annals of Agricultural Research, 2024)
A field experiment was conducted at District Seed Farm (AB Block), Kalyani under Bidhan Chandra Krishi Viswavidyalaya during the winter season of 2020 and 2021 in the upland situation to assess the performance of wheat productivity under different sowing time with different dose of nutrient along with FYM and growth retardent. The experiments were laid out in a split-plot design with four sowing time (30th October, 15th November, 30th November and 15thDecember) in main plot and four nutrient management options (RFD, RFD + FYM (@ 10 t/ha), 150 % RFD + FYM (@ 10 t/ha) and 150 % RFD + FYM (@ 10 t/ha) + GR) in subplots replicated thrice. All yield attributes were significantly influenced by the date of sowing. Effective tillers improved significantly with the 30thOctober and showed parity only with 15thNovember. Observation revealed that 29.4 and 26.1% more effective tiller/m2 was recorded with this treatment over the extreme late sown conditions i.e. 15thDecember. The maximum and significantly more grain yield was obtained with 15th November (48.39q/ha) and showed parity with earlier sowing i.e. 30th October and was statistically superior to other treatment measures. The resulted in 13.9 and 38.73 % more yield over 30th November and 15thDecember sowing, respectively. Application of 150 % RFD + FYM(@10 t/ha) + GR, registered 20.3 and 16.0 % more grain yield over RFD and RFD + FYM(@10 t/ha). Economics revealed that, higher net return ( 36.95 x 103) and B:C ratio (1.72) observed with 15thNovember and was followed by 30th October (Table 2). With various nutrient management more net return found with the 150 % RFD + FYM (@ 10 t/ha) + GR(36.11x 103) with B:C ratio of 1.65 only